Platelet Physiology - Gremmel, Thomas; Frelinger, Andrew L., III; Michelson, Alan D. (Seminars in Thrombosis and Hemostasis, 2024)
Platelets are the smallest blood cells, numbering 150 to 350 × 109/L in healthy individuals. The ability of activated platelets to adhere to an injured vessel wall and form aggregates was first described in the 19th century. Besides their long-established roles in thrombosis and hemostasis, platelets are increasingly recognized as pivotal players in numerous other pathophysiological processes including inflammation and atherogenesis, antimicrobial host defense, and tumor growth and metastasis. Consequently, profound knowledge of platelet structure and function is becoming more important in research and in many fields of modern medicine. This review provides an overview of platelet physiology focusing particularly on the structure, granules, surface glycoproteins, and activation pathways of platelets.
Keywords: platelet function; platelet structure; platelet granules; platelet surface glycoproteins; platelet activation pathways; platelet physiology; review